Evaluation of MBKM Program Implementation in Elementary Schools - Priyono Tri Febrianto; Irena Yolanita Maureen; Bachtiar Sjaiful Bachri (LPPM Universitas Trunojoyo Madura, 2023)
The two most important things in education in Indonesia today are 'Freedom to Learn' and driving teachers. This study aims to provide an overview of the implementation of the 'Freedom to Learn' program at the elementary school level, as well as to explain the various innovations, obstacles encountered, and solutions made by the school and teachers as teaching boards. This study uses descriptive quantitative research methods, with 166 respondents from 21 districts/cities in East Java. The results of this study show that; (1) the successful implementation of the 'Freedom to Learn' program can be seen from the ability of schools and teachers to develop teaching creativity during the learning process. (2) Most of the obstacles encountered during program implementation stem from the inability of the teacher to provide learning methods that are right on target, skills that are not sufficient and the limited ability of students to accept the 'transfers of knowledge' provided by the teacher. This study concludes that schools and teachers can optimize learning innovations by using various methods adapted to the student's environment, such as; applying student center learning learning methods, exposition discovery learning methods, individual group learning methods, brainstorming methods, blended learning, and other methods that can improve students' skills and creativity, by implementing fun teaching and learning programs.